2001
DOI: 10.1007/bf01470996
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotypic antibody (Ab2) vaccines: Coupling of Ab2 BR3E4 to KLH increases humoral and/or cellular immune responses in animals and colorectal cancer patients

Abstract: The colorectal carcinoma (CRC)-associated CO17-1A/GA733 antigen (Ag) has been the target of a phase II/III randomized trial of passive immunotherapy with monoclonal antibody CO17-1A (Ab1), and phase I active immunotherapy trials with polyclonal anti-idiotypic antibodies (Ab2) mimicking the CO17-1A or GA733 epitope of the Ag. However, monoclonal rat Ab2 BR3E4 directed against Ab1 CO17-1A was superior to polyclonal Ab2 in inducing antigen-specific humoral and cellular immune responses in mice and rabbits. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Over about 20 years, scientists at the Wistar Institute have tenaciously brought to sequential clinical application passive immunotherapy with murine CO17-1A mAb and active immunotherapy with polyclonal goat anti-Id antibodies produced against the same CO17-1A mAb, which mimics the CRC-associated antigen above (Birebent et al, 2001a, b). Results of the former approach were substantially modest, whereas with the latter strategy anti-anti-Id humoral immune responses were systematically documented ever since the first trial was concluded, and encouraging partial responses were also described.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Over about 20 years, scientists at the Wistar Institute have tenaciously brought to sequential clinical application passive immunotherapy with murine CO17-1A mAb and active immunotherapy with polyclonal goat anti-Id antibodies produced against the same CO17-1A mAb, which mimics the CRC-associated antigen above (Birebent et al, 2001a, b). Results of the former approach were substantially modest, whereas with the latter strategy anti-anti-Id humoral immune responses were systematically documented ever since the first trial was concluded, and encouraging partial responses were also described.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Once again, the actual clinical impact of the strategy could not be completely ascertained, inasmuch as all patients had undergone primary tumor and lymph node metastases surgical removal before receiving immunotherapy (Somasundaram et al, 1995). More recently, a rat mAb directed against CO17-1A has shown clear superiority over the goat polyclonal antibodies above in inducing antigen-specific, humoral and cellular immune responses; these responses also benefited of conjugation of such a mAb with keyhole limpet hemocyanin (Birebent et al, 2001a, b). Subsequent studies have also proved that when molecularly cloned in a baculovirus, the GA733 epitope is more immunogenic than its mimicking anti-Id mAb counterpart, both in terms of humoral and cellular immune responses elicited (Birebent et al, 2001a, b).…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Original strategies involved the coupling of vaccines to anti-Ig antibodies (Abs) [1] or MHC class II molecules [2] to develop an adjuvant-free method to enhance vaccine uptake. More recently, using Abs to target dendritic cells (DCs), as with DEC205 mAb, has enhanced immunogenicity to HIV [3] and plague LcrV [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both the described Ab- [1][5] and DC-targeting methods [3][7] adopt a targeting strategy for a specific host cell receptor. To improve mucosal immunity, strategies also have focused on targeting microfold (M) cells [8], a specialized epithelium present on the luminal surface of the Peyer's patches (PPs) or nasal-associated lymphoid tissue (NALT).…”
Section: Introductionmentioning
confidence: 99%